Synthesis of nanostructured Nickel compounds on conductive metallicsubstrates - Portillo, J.G. (2019)
Nickel hydroxide, oxide, and sulfide films were synthesized on conductive Ni metallic substrates by solidvapor reactions, calcination and hydrothermal methods. The synthesized films were characterized by XRD, XPS, FE-SEM, UV–Vis Spectroscopy and Cyclic Voltammetry (CV). The morphological analyses of Ni(OH)2 and NiO films showed flower-like nanostructures with thicknesses from 20 to 40 nm; meanwhile the NiS films exhibits nano-granular morphology. All films showed high optical reflectance in the visible region and a sharp absorption edge below 400 nm. The specific capacitance of the Nickel compound ranges from 134 to 311 mF cm 2 (at 20 mV s 1) suggesting potential as conductive electrodes for energy storage and electrochemical conversion cells.